The complete mitochondrial genome of the Antarctic springtail Cryptopygus antarcticus (Hexapoda: Collembola) - Nardi Francesco; Convey Peter; Comandi Sara; Carapelli Antonio; Frati Francesco (BMC Genomics, 2008)
Abstract Background Mitogenomics data, i.e. complete mitochondrial genome sequences, are popular molecular markers used for phylogenetic, phylogeographic and ecological studies in different animal lineages. Their comparative analysis has been used to shed light on the evolutionary history of given taxa and on the molecular processes that regulate the evolution of the mitochondrial genome. A considerable literature is available in the fields of invertebrate biochemical and ecophysiological adaptation to extreme environmental conditions, exemplified by those of the Antarctic. Nevertheless, limited molecular data are available from terrestrial Antarctic species, and this study represents the first attempt towards the description of a mitochondrial genome from one of the most widespread and common collembolan species of Antarctica. Results In this study we describe the mitochondrial genome of the Antarctic collembolan Cryptopygus antarcticus Willem, 1901. The genome contains the standard set of 37 genes usually present in animal mtDNAs and a large non-coding fragment putatively corresponding to the region (A+T-rich) responsible for the control of replication and transcription. All genes are arranged in the gene order typical of Pancrustacea. Three additional short non-coding regions are present at gene junctions. Two of these are located in positions of abrupt shift of the coding polarity of genes oriented on opposite strands suggesting a role in the attenuation of the polycistronic mRNA transcription(s). In addition, remnants of an additional copy of trnL(uag) are present between trnS(uga) and nad1. Nucleotide composition is biased towards a high A% and T% (A+T = 70.9%), as typically found in hexapod mtDNAs. There is also a significant strand asymmetry, with the J-strand being more abundant in A and C. Within the A+T-rich region, some short sequence fragments appear to be similar (in position and primary sequence) to those involved in the origin of the N-strand replication of the Drosophila mtDNA. Conclusion The mitochondrial genome of C. antarcticus shares several features with other pancrustacean genomes, although the presence of unusual non-coding regions is also suggestive of molecular rearrangements that probably occurred before the differentiation of major collembolan families. Closer examination of gene boundaries also confirms previous observations on the presence of unusual start and stop codons, and suggests a role for tRNA secondary structures as potential cleavage signals involved in the maturation of the primary transcript. Sequences potentially involved in the regulation of replication/transcription are present both in the A+T-rich region and in other areas of the genome. Their position is similar to that observed in a limited number of insect species, suggesting unique replication/transcription mechanisms for basal and derived hexapod lineages. This initial description and characterization of the mitochondrial genome of C. antarcticus will constitute the essential foundation prerequisite for investigations of the evolutionary history of one of the most speciose collembolan genera present in Antarctica and other localities of the Southern Hemisphere.